Selecting doctors for postgraduate training in paediatrics using a competency based assessment centre. Issue 5 (21st April 2006) - Randall, R; Davies, H; Patterson, F; Farrell, K
Abstract : The design and implementation of an assessment centre in the South Yorkshire and South Humberside deanery for selecting doctors into postgraduate training in paediatric medicine is described. Eleven competency domains were identified in the job analysis. An assessment centre comprising of four exercises was implemented to assess candidates. There were modest relationships between candidates' performance on the various assessment centre exercises. Outcomes based on interview performance were related to, but not the same as, outcomes based on the combined results of the three other assessment centre exercises. Candidates perceived the assessment centre to be a fair selection method. It is concluded that an assessment centre approach to SHO recruitment is feasible and provides a greater breadth and depth of information about candidates than does a structured interview.